Topical Delivery of Meloxicam using Liposome and Microemulsion Formulation Approaches - Julia Zhang; Anna Froelich; Bozena Michniak-Kohn (Pharmaceutics, 2020)
The aim of this study is to develop, characterize and compare conventional liposome, deformable liposome (transfersome) and microemulsion formulations as potential topical delivery systems for meloxicam. Liposomes were characterized in terms of vesicle size, zeta potential and entrapment efficiency. For microemulsions, particle size, electrical conductivity and viscosity studies were performed to assess the structure of the investigated systems. An ex vivo skin permeation study has been conducted to compare these formulations. The dermal and transdermal delivery of meloxicam using these formulations can be a promising alternative to conventional oral delivery of non-steroidal anti-inflammatory drugs (NSAIDs) with enhanced local and systemic onset of action and reduced side effects.